Management of Posterior Fossa Tumors in Adults Based on the Predictors of Postoperative Hydrocephalus - Zhang, Chengda; Zhang, Tingbao; Ge, Lingli; Li, Zhengwei; Chen, Jincao (Frontiers in Surgery, 2022)
Objective This study aims to identify the predictors of postoperative hydrocephalus in patients with posterior fossa tumors (PFTs) and guide the management of perioperative hydrocephalus. Methods We performed a single-institution, retrospective analysis of patients who underwent resection of PFTs in our department over a 10-year period (2011–2021). A total of 682 adult patients met the inclusion criteria and were divided into either a prophylactic external ventricular drainage (EVD) group or a nonprophylactic-EVD group. We analyzed data for the nonprophylactic-EVD group by univariate and multivariate analyses to identify predictors of postoperative acute hydrocephalus. We also analyzed all cases by univariate and multivariate analyses to determine the predictors of postoperative ventriculoperitoneal (VP) shunt placement. Results Tumor infiltrating the midbrain aqueduct [P = 0.001; odds ratio (OR) = 9.8], postoperative hemorrhage (P < 0.001; OR = 66.7), and subtotal resection (P = 0.006; OR = 9.3) were independent risk factors for postoperative EVD. Tumor infiltrating the ventricular system (P < 0.001; OR = 58.5) and postoperative hemorrhage (P < 0.001; OR = 28.1) were independent risk factors for postoperative VP shunt placement. Conclusions These findings may help promote more aggressive monitoring and earlier interventions for postoperative hydrocephalus in patients with PFTs.